Gender Differences in Attitudes and Perceptions of Human Trafficking: Are They Driven by Knowledge Gaps? - Hansen, Michael A.; Johansson, Isabelle (Informa UK Limited, 2025)
Despite growing awareness of human trafficking, research has yet to explore whether attitudes and knowledge about this issue are affected by gender. This study fills that gap by analyzing gender differences in public perceptions of human trafficking using a nationally representative U.S. sample (N = 776). The findings reveal that women are more likely than men to associate human trafficking with a wider range of vulnerable groups and forms of exploitation, perceive it as more severe, and are more likely to attribute it to systemic causes, including gender inequality and institutional corruption. Though knowledge predicted attitudes, men and women demonstrated no significant gender differences in factual knowledge. These results suggest that social and cultural influences shape gendered perceptions of human trafficking, underscoring the importance of integrating gender perspectives into anti-trafficking awareness campaigns and public education efforts.